When a function is translated, it means the function is moved from one point to another.
The resulting function g(x) is: [tex]g(x) = (x + 1)^2 + 3[/tex]
Given that:
[tex]f(x) = x^2[/tex]
When the function is translated 3 units up, the rule is:
[tex](x,y) \to (x,y+3)[/tex]
So, we have:
[tex]f'(x) = x^2 + 3[/tex]
When the function is translated 1 unit left, the rule is:
[tex](x,y) \to (x + 1,y)[/tex]
So, we have:
[tex]g(x) = (x + 1)^2 + 3[/tex]
Hence, the resulting function g(x) is:
[tex]g(x) = (x + 1)^2 + 3[/tex]
See attachment for the graphs of f(x) and g(x)
Read more about translations at:
https://brainly.com/question/12463306